Caregiver Burden and Needs in Frontotemporal Dementia. (December 2013) - Diehl-Schmid, Janine; Schmidt, Eva-Maria; Nunnemann, Sabine; Riedl, Lina; Kurz, Alexander; Förstl, Hans; Wagenpfeil, Stefan; Cramer, Barbara
Background: It is well known that burden among caregivers of patients with frontotemporal dementia (FTD) is high. However, little is known about the specific problems, the factors that contribute to caregiver burden, and the needs of the FTD caregivers—particularly those needs that are accessible by external support strategies. Objective: We developed a standardized questionnaire that addressed burdens, problems, and the actual needs of FTD caregivers. A total of 94 caregivers were interviewed. Results: It appears that changes in the patients' behavior and in the interpersonal relations between caregivers and patients are associated with caregiver depression. The most important needs and requests of the caregivers included information and psychosocial support through educated staff, financial support as well as the education of medical staff about the disease. Conclusions: Support strategies should focus on information and psychosocial support. Given the low prevalence of FTD, internet- and telephone-based strategies appear suitable.